Influence of nonlocal on a rotating thermoelastic medium with diffusion and double porosity - Doaa M. Salah; A. M. Abd-Alla; S. M. M. El-Kabeir (Scientific Reports)
Abstract In this paper, we have studied the thermodynamical interactions in a two-dimensional thermoelastic diffusion in homogeneous isotropic medium with nonlocal, rotation and double porosity in the context of Green–Lindsay theory. A thermal load was applied to the medium’s outer free surface. By employing the Lame’s potential and normal mode technique, we derived analytical expressions for field quantities such as thermal stresses, displacement components, temperature field, equilibrated stresses and diffusion. Numerical computations conducted using MATLAB programming for a specific material, illustrated the results. Several graphs are presented to examine the effects of time, nonlocal parameter, double porosity and rotation. Furthermore, comparisons are made between CT, LS, and GL theories. The theoretical and numerical results were found to be in close agreement. Computer-simulated numerical results are presented through graphical representations illustrating the physical quantities for both the nonlocal thermoelastic half-space with double porosity under the influence of rotation. Additionally, the results offer valuable insights for fields such as geophysics and biomedical engineering, where the interaction between multiple fields is critical. Comparative plots further illustrate the nonlocal parameter, time, rotation and porosity effects on the wave propagation properties.